Mudanças identificáveis no nível de Hemerobia resultantes da dinâmica do uso da terra na Bacia Hidrográfica do Rio Grande Comitán (Chiapas, México). uma análise do período 1999-2019 - Aguilar López, Flor Magali (2020)
The intensification of agricultural and non-agricultural anthropic uses in a watershed generates a high dependence on the consumption of local natural resources, in contrast to the increase in the condition of hemeroby and the reduction of the capacity for self-regulation, due to the decline in naturalness. This research evaluated the changes in the hemeroby levels resulting from the land use and cover dynamic, using the Index Distance to Nature (D2N) as a tool for the environmental monitoring and planning of the Rio Grande Comitán watershed (Chiapas, Mexico), over the 20-year period (1999 - 2019). The classification and quantification of the land use and cover of the watershed were obtained based on the images Land-Sat-5 (1999 and 2009) and Land-Sat 8 (2019), through the Semi-automatic Classification module in ArcGis software 10.5. The total area of the land uses natural class (native vegetation, wetlands and riparian forest) reduced, in contrast to the increase in anthropic agricultural use (agriculture and bare soil), as the most representative land use class, over the 20-year period (1999 to 2019). Five (5) hemeroby levels were identified for the Rio Grande Comitán watershed, with some adaptations to contemplate the biotic and cultural local characteristics, whose quantitative variations in the areas evidenced the anthropogenic pattern trajectory, over the period 20 years. This scenario resulted from the increase of the areas of the Cultural hemeroby level (agriculture and bare soil), Artificial (urban area and road network) and Artificial with natural elements (rural settlements, mining and airport), in contrast to the reduction of the areas of the Near to Natural hemeroby level (natural areas and aquatic environments) and Altered hemeroby level (pastures), over the period of 20 years. The analysis of the land use transition matrix, between the years 1999 - 2009/2009 - 2019, and 1999 - 2019, showed that, over the period of 20 years, about 40% of the total watershed area remained with the same spatial composition of land uses. In the remaining total area (60%), the main transition values were represented by the reduction of the areas of the hemeroby level Near to Natural and Altered, and a consequent increase in the areas of Cultural and Artificial / Artificial with natural elements hemeroby levels. The results of the Index Distance to Nature(D2N), over the 20-year period, confirmed the dynamics of the anthropization process of the Rio Grande Comitán watershed, in which the Near to Natural landscape was reduced and replaced by an anthropogenic landscape, related to the expansion of agriculture and urbanization. The D2N values, over the 20-year period, for the watershed area and for the municipal territories of Comitán de Domíngez, La Independencia and La Trinitária proved to be easy to understand and interpret, in addition to enabling comparative conditions in the international and national context, since the index calculation is related to land use values with different themes and at different spatial scales. The D2N demonstrated the potential to support the decision-making process regarding the environmental planning and monitoring of the watershed, adding the issue of developing a sustainable land use policy. The quantitative spatio-temporal analysis of the dynamics of D2N values, grouped into three and five categories, showed the main changes in the trajectory of anthropic activities that occurred in the Rio Grande Comitán watershed, in the period of 20 years. Particularly, for the 0.35 - 1 range, corresponding to human activities associated with agriculture and urbanization. Quite peculiar to the fraction of urbanization related to the performance of rural settlements (Ejidos), in the form of spaces legally instituted for the effective insertion of campesino and indigenous communities, as part of the history of the issue of land tenure. The reported scenario indicates a trend towards the watershed sustainability, over time, due to the gradual and continuous reduction of naturalness, over the 20-year period. The dynamics of the watershed anthropogenic pattern proves to be extremely dependent on agricultural development policies, as well as on the historical and social context of land tenure in the Rio Grande Comitán watershed region.